Chemical formula depiction using web service - Peter Cirbes; Dušan Dugáček; Pavel Horovčák (Acta Montanistica Slovaca, 2009)
Accurate minerals’ chemical formulas depiction in websites requires an adequate working out of their representation. Within the latest approaches and technologies lies a SOA (Service Oriented Architecture), realized predominantly by WS (Web Service). The paper is devoted to SOA utilization in problem solution of chemical formulas depiction in internet environment by creation for this purpose intended web service. The application functionality is documented by its calling in testing website. In this way the SOA carries possibility of executive, effective, freely utilizable and interactive web applications creation.